STUDI KINERJA CAMPURAN ASPAL PORUS DENGAN PENAMBAHAN BAHAN ADDITIVE REDISET LQ-1106 - Eza Marizka; Miftahul Fauziah; Subarkah (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2022)
Porous asphalt is an asphalt mixture with high porosity to reduce the potential waterlogging and increase the roughness of the road surface. However, porous asphalt mixture has shortcomings in terms of strength and durability. This paper presents laboratory testing results of the effect of adding Rediset LQ-1106 additive on the performance of a porous asphalt mixture. The research was started with the determination of the optimum asphalt content. Then, the test object was made with Rediset LQ-1106 using variations in 0%, 1%, 2%, and 3% of the optimum asphalt content and carried out the Marshall test, Immersion Test, Indirect Tensile Strength, Tensile Strength Ratio, and Wheel Tracking. The test results show that adding 1% of Rediset LQ-1106 resulted in the optimum performance of porous asphalt compared to other grade additions. This performance is evidenced by the increase in the mixture stability value by 18.62%, the Indirect Tensile Strength value of 20.14%, the dynamic stability value of 35.88%, and the most negligible deformation speed compared to porous asphalt, which does not use Rediset LQ-1106. However, the Index Retained Strength, and Tensile Strength Ratio tests did not significantly increase performance.